Lutas e a formação de professores de educação física: reflexos na atuação profissional de docentes da rede municipal de educação de Belém - PA - Marcio Antonio Raiol dos Santos; Pedro Paulo Souza Brandão (Universidade Estadual do Oeste do Paraná, 2018)
This study aims to investigate the reflexes of the formation of physical education teachers in the professional work of teachers that work the knowledge of the fights in the Municipal Education Network of Belém-PA. It was configured based on a field research with qualitative nature that had as participants all the physical education teachers of the Municipal Education Network of Belém-PA who works in schools that attend the final years of elementary school. As a data collection instrument, a form was used and, as a data analysis technique, we opted for content analysis. The results revealed that: a) most of the teachers had contact with the content of the fights in the formation through disciplines, in a fragmented way in modalities without correlation between these and, with a technical perspective; b)Teachers treat pedagogically the content fights in three ways: i) fragmented teaching by autonomous way (specific modalities taught by teachers); ii) fragmented teaching in a dependent way (specific modalities taught by specialists/fighters); iii) global education (common principles of the fights didatized in a ludic way); c) learning of discipline and social values are the main benefits attributed to content by teachers. With this, we can conclude that the lack of domain of didactic-methodological tools for the teaching of the fights, by the teachers, is a reflection of the way in which they had contact with this content in the formation, revealing its deficiency and the need to qualify it, to reflect positively on the professional performance of teachers in the school.